The Behavioral Economics of Drunk Driving: Case Study of Nakhon Si Thammarat Province - Penpong, Manolee Sripaoraya; Siriphon, Siriphon; Muknag, Jutharat (Journal of Applied Economics and Management Strategy [eISSN 2985-1408], 2024)
Alcohol consumption has contributed to problems related to accidents caused by drunk driving behavior, as the majority of accidents involve drivers who have consumed alcohol or other intoxicating substances. The consequences include injuries, disabilities, and fatalities. When considering the proportion of traffic accidents caused by drunk driving in the southern region, it was found that Nakhon Si Thammarat Province ranked second in terms of the highest proportion of drunk driving behavior (Royal Thai Police, 2016). Therefore, Nakhon Si Thammarat was selected as the research area with the objective of studying the economic behavior of decisions related to drunk driving. The data used in this research were collected from a survey of 100 individuals who were placed under probation for drunk driving in Nakhon Si Thammarat Province. The statistical methods used for analysis include mean, standard deviation, percentage, and Logit model. The study of economic behavior in decisions related to drunk driving created three hypothetical scenarios. The results showed that in Scenario 1, when drinking with an alcohol content of not more than 50 milligrams percent. The results showed that the probability of choosing a motorcycle to travel was 0.8961. Scenario 2, If you consume more than 50 milligrams of alcohol, but there are no legal requirements. The sample group chose to travel by car equaling 0.99757. Scenario 3, When the alcohol content of the drink exceeds 50 milligrams per cent and there is a legal requirement to drive a vehicle (illegally). The probability of the sample group choosing a public bus was 0.8866. Therefore, based on the research findings, efforts to reduce the behavior and decision-making related to drunk driving should focus on enforcing drunk driving laws, strictly monitoring alcohol levels during driving, educating the public on the legal penalties for drunk driving, and raising awareness of the consequences of driving under the influence of alcohol.